Metabolism of formycin B by Leishmania amastigotes in vitro. Comparative metabolism in infected and uninfected human macrophages (The Rockefeller University Press, 1983)
Formycin B is metabolized by cutaneous Leishmania amastigotes within cultured human macrophages to give formycin B 5'-monophosphate and formycin A 5'-mono-, di-, and triphosphates. Formycin A is also incorporated into RNA. The activity of formycin B against amastigotes was correlated with the levels of formycin A metabolites formed in the parasites. Uninfected macrophages also convert formycin B into the same products, but the levels are markedly lower than those seen in infected macrophages. The results suggest that a sufficient therapeutic index exists to warrant consideration of formycin B as an anti-leishmanial drug in humans.